2021
DOI: 10.1161/jaha.120.020606
|View full text |Cite
|
Sign up to set email alerts
|

Number and Replating Capacity of Endothelial Colony‐Forming Cells are Telomere Length Dependent: Implication for Human Atherogenesis

Abstract: Background Short leukocyte telomere length (TL) is associated with atherosclerotic cardiovascular disease. Endothelial repair plays a key role in the development of atherosclerosis. The objective was to examine associations between TL and proliferative dynamics of endothelial colony‐forming cells (ECFCs), which behave as progenitor cells displaying endothelial repair activity. Methods and Results To isolate ECFCs, we performed a clonogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Atherosclerosis is an inflammatory process that develops in response to endothelial injury [35,36]. Multiple lines of evidence indicate that ECFCs play an important role in repairing injured vessels and in atherogenesis [8]. Conflicting data, however, exist regarding ECFC changes in PLHIV and their role in HIV-associated CVD development [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atherosclerosis is an inflammatory process that develops in response to endothelial injury [35,36]. Multiple lines of evidence indicate that ECFCs play an important role in repairing injured vessels and in atherogenesis [8]. Conflicting data, however, exist regarding ECFC changes in PLHIV and their role in HIV-associated CVD development [37].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial colony-forming cells (ECFCs), formerly known as late endothelial progenitor cells (EPCs), are derived from precursor cells that are activated upon vascular injury to promote angiogenesis, EC rejuvenation, and vascular repair [7]. There is evidence suggesting that early stages of atherogenesis are associated with decreased ECFC functionality and reduced ECFC counts [8]. Interestingly, it has been shown that PLHIV have decreased ECFC numbers and impaired ECFC functionality [9].…”
Section: Introductionmentioning
confidence: 99%
“…ECFC senescence can be influenced by environmental systemic or local factors as well as by telomere integrity. Interestingly, we recently reported that formation and number of ECFC as well as their replating capacity are associated with telomere length [ 43 ]. ASCVD patients display shorter telomere length in leukocytes [ 44 ] and this telomere length is correlated with telomere length in ECFC [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we recently reported that formation and number of ECFC as well as their replating capacity are associated with telomere length [ 43 ]. ASCVD patients display shorter telomere length in leukocytes [ 44 ] and this telomere length is correlated with telomere length in ECFC [ 43 ]. Then, short telomere length in these cells could explain the observed senescence phenotype and reflect their diminished reparative capacity as previously observed in hematopoietic stem cells [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA quantity was assessed by spectrophotometry (Nanodrop, Thermo Fisher Scientific, Waltham, MA, USA). DNA samples passed integrity testing using a 1% (wt/vol) agarose gel prior to performing the TL measurement by Southern blot analysis of the terminal restriction fragments, as described previously [ 19 ]. Briefly, DNA samples were treated overnight with restriction enzymes HinfI and RsaI (Roche Diagnostics GmbH, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%